Deteksi objek manusia pada image dengan metode Thinning Berdasarkan local maxima - Mawaddah Harahap; Erik Sartana Agustia; Muhammad Marsyal Lubis; Apriandi Apriandi; Alvin Anggara (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The aim to detection human object is to identifying human object in image. There is a change human object affected by internal factors like face expression, body shape, skin color, and movement body and affected by external factor likes lighting condition, background which varies and corner taking image. The detect human object towards some condition likes obtained on image which containts more than one object, and object size which varies in image. The research aim to analizying and designing a application for detect human object in image. Thinnging algorithm used to introduction pattern human object from a image for another image in order to equalize object pixel to detection maximum. The local maxima used as function for maximize searching pixel on object in image for make it easier and faster to detect image